The parasite-stress theory of values and sociality : infectious disease, history and human values worldwide - Thornhill, Randy (Springer International Publishing, 2014)
Why do some people pray more than others? Why do some people prefer to be with healthier-looking people? Why are some people more conservative than others? Why does the prevalence of violence vary across the world? Why are some countries poor while others are increasingly wealthy? Why are some countries mired in corruption? Randy Thornhill and Corey L. Fincher argue that the answers to these questions, and many more about the human condition, come down to understanding how infectious diseases have shaped human behavior and psychology. Paramount to this view is that other human beings are often the harbinger of infectious diseases, which has profound implications for the evolution of human sociality. In The Parasite-Stress Theory of Values and Sociality: Infectious Disease, History and Human Values Worldwide, the authors bring a wealth of evidence from across many scholarly fields, much of which has been produced in the last decade, to support this claim. Read this book to learn how infectious diseases have shaped human emotions, morality, political and cultural values, personality, family ties, mate preferences and sexuality, religiosity, intergroup psychology, governmental systems, trade, war, economic development, intelligence and innovation, and biodiversity, and more. Randy Thornhill serves as Distinguished Professor of Biology at the University of New Mexico. Corey L. Fincher is an Assistant Professor in Psychology at the University of Warwick.